Synthesis of benzo[f]quinazoline-1,3(2H,4H)-diones - de Abreu, Ruben Manuel Figueira; Ehlers, Peter; Langer, Peter (Beilstein Journal of Organic Chemistry, 2024)
We report the synthesis of polycyclic uracil derivatives. The method is based on palladium-catalysed Sonogashira–Hagihara and Suzuki–Miyaura cross-coupling reactions followed by Brønsted acid-mediated cycloisomerisation. The developed methodology tolerates various functional groups and leads to moderate up to quantitative yields of the final products. The impact of different functional groups on the optical properties was studied by UV–vis and fluorescence spectroscopy.
Keywords: cross-coupling; cyclization; heterocycles; palladium